The role of perfectionism in predicting athlete burnout, training distress, and sports performance: A short-term and long-term longitudinal perspective - Kveton, P.; Jelínek, M.; Buresová, I. (Journal of Sports Sciences, 2021)
This study examined the influence of perfectionistic strivings and perfectionistic concerns on athlete burnout and two key indicators of overtraining syndrome (training distress and subjectively perceived sports performance) using cross-sectional (N = 228), short-term (a 3-month interval, N = 93) and long-term (a 1-year interval, N = 83) longitudinal designs on a sample of adolescent athletes. In the cross-sectional analyses, sequential regressions revealed that perfectionism was a significant predictor of athlete burnout and both indicators of overtraining. In the three-month longitudinal perspective, both dimensions of perfectionism (strivings and concerns) contributed to the prediction of change in burnout and sports performance, but not training distress. When the one-year longitudinal relationships were regarded, only perfectionistic strivings significantly predicted decrease in burnout, and, for sports performance, the predictive power of both dimensions of perfectionism was even more pronounced when compared to the three-month longitudinal data.